Burmeistera quimiensis (Lobelioideae, Campanulaceae): A new species from the Cordillera del Cóndor range in southeast Ecuador - Mashburn, Brock; Pérez, Álvaro J.; Persson, Claes; Zapata, Nicolás; Cevallos, Daniela; Muchhala, Nathan (Phytotaxa, 2020)
A new taxon belonging to the genus Burmeistera (Campanulaceae, Lobelioideae) is described from El Quimi Biological Reserve in Morona Santiago Province, southeast Ecuador. Burmeistera quimiensis is characterized by its red-violet stems and veins, spiral phyllotaxy, bullate, ascending leaves with a revolute margin, puberulous abaxial leaf surface, cupuliform hypanthia, and thick-walled white to red-violet fruits with reflexed pedicels. Photos of the new species are given, as well as a distribution map of known collection localities, and its relationships with other species are discussed.